The Impact of Digital Leadership on Corporate Social Responsibility: A Research in Bursa - Kustepe, Veli; Ruzgar, Nilufer (European Scientific Journal, ESJ, 2026)
In today’s business world, digitalization has become a critical factor for businesses to achieve sustainable competitive advantage. By strategically directing the use of technology, digital leaders both increase internal organizational efficiency and strengthen relationships with external stakeholders. In this context, the question of how digital leadership impacts corporate social responsibility (CSR) practices gains importance. In an era of accelerating digitalization, the concept of digital leadership plays a crucial role in businesses’ sustainability strategies and achieving their goals. Digital leadership not only manages digital transformation processes but can also shape CSR activities. By using technology as a strategic tool, digital leaders support CSR practices and increase the effectiveness of projects in this area. The purpose of this thesis is to examine the relationship between digital leadership and CSR, exploring the impact of digital leadership on CSR and the interaction between these two concepts. Within the scope of the research, a survey form consisting of demographic questions, the 18-item Corporate Social Responsibility Scale (Türker, 2006), and the 9-item Digital Leadership Scale developed by Büyükbeşe, Dikbaş, Klein, and Batuk Ünlü (2022) was created and sent to potential participants via e-mail. Responses to the survey were received from 332 participants, and the obtained data were analyzed using the SPSS 26.0 package program. In addition to descriptive analyses, Simple Linear Regression Analysis was applied to reveal the relationships between the variables. The analysis findings indicate a positive and statistically significant relationship (p<0.05) between digital leadership and CSR perception.